2021
DOI: 10.3390/biomedicines9121854
|View full text |Cite
|
Sign up to set email alerts
|

The Local Neuropeptide System of Keratinocytes

Abstract: Neuropeptides have been known for over 50 years as chemical signals in the brain. However, it is now well established that the synthesis of this class of peptides is not restricted to neurons. For example, human skin not only expresses several functional receptors for neuropeptides but, also, can serve as a local source of neuroactive molecules such as corticotropin-releasing hormone, melanocortins, and β-endorphin. In contrast, an equivalent of the hypothalamic-pituitary axis in the oral mucosa has not been w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…β-endorphin has a local effect for pain management [ 140 ]. α-MSH serves locally to stimulate melanocytes for pigment production and regulate inflammation and extracellular matrix homeostasis through the receptor MC1R [ 141 ]. The other protein and non-protein groups reflect single reports of non-related secretions, including hyaluronan, which is an important component of the extracellular matrix.…”
Section: Resultsmentioning
confidence: 99%
“…β-endorphin has a local effect for pain management [ 140 ]. α-MSH serves locally to stimulate melanocytes for pigment production and regulate inflammation and extracellular matrix homeostasis through the receptor MC1R [ 141 ]. The other protein and non-protein groups reflect single reports of non-related secretions, including hyaluronan, which is an important component of the extracellular matrix.…”
Section: Resultsmentioning
confidence: 99%
“…Skin is considered as an important peripheral neuro-endocrine-immune organ closely linked to the central regulatory systems. The local synthesis of neuropeptides also takes place in keratinocytes ( 24 ). Thus, we further examined the expression of neuropeptides in keratinocytes, showing that glutamic acid or aspartic acid induced elevation of VIP , PACAP , CGRP α , and CGRP β in HaCaT keratinocytes in a dose-dependent manner ( Figure 5, C and D ), whereas leucine did not increase the expression of neuropeptides ( Supplemental Figure 4C ).…”
Section: Resultsmentioning
confidence: 99%
“…We speculated that the expression of VIP induced by amino acids could be an important cause of neurogenic vasodilation in rosacea. In addition, evidence for a neuropeptidergic system in skin keratinocytes was reported ( 24 ). Here, we demonstrated that VIP , PACAP , CGRP α , and CGRP β , mediating angiogenesis and vasodilation in skin, were all upregulated in keratinocytes by glutamic acid and aspartic acid.…”
Section: Discussionmentioning
confidence: 99%
“…The endogenous opioid system consists of neuropeptides (endorphins, enkephalins, endomorphins, and dynorphins) and opioid receptors (ORs, µ, δ, and κ) (Cirillo, 2021). δ-OR, κ-OR, µ-OR, and nociceptin/orphanin FQ peptide receptor (NOP) are expressed on KCs (Bigliardi et al, 1998(Bigliardi et al, , 2015Andoh et al, 2004;Tominaga et al, 2007).…”
Section: Endogenous Opioid Systemmentioning
confidence: 99%